Cutaneous Manifestations Associated with COVID-19 Infection. A Review of the Literature. - Benavides-Tulcán, Eine Yesid (2022)
The SARS-CoV-2 infection has spread rapidly until it has been classified as a pandemic. COVID-19 disease can affect different systems, the respiratory system being the most compromised, however it can injure other organs, including the skin; dermatological semiology is heterogeneous and complex, and it has been related to the immune response to the nucleotides of the new betacoronavirus or eruptions secondary to sequelae of the infection. For this review of the narrative type literature, an exhaustive search of scientific literature was carried out in order to describe the most common skin manifestations in children and adults, also with the objective of characterizing them, where it was found that manifestations have been described in adults skin types: vesicular rashes, urticarial eruptions, maculopapular rashes and livedoid/necrotic lesions, and lesions such as erythematous maculopapular rash, chilblains, and erythema multiforme have been described in children. The most common symptom manifested is mild pruritus, and mucosal involvement is rare. Knowledge of the cutaneous manifestations of COVID-19 is important since the foregoing may allow an early diagnosis together with an impact on morbidity and mortality rates.